The Prevalence of Islet Autoantibodies in Children and Adolescents With Type 1 Diabetes Mellitus: A Global Scoping Review - Ross, Carlo; Ward, Zachary J.; Gomber, Apoorva; Owais, Maira; Yeh, Jennifer M.; Reddy, Ché-L.; Atun, Rifat (Frontiers in Endocrinology, 2022)
Background and Purpose Pancreatic islet autoantibodies (iAb) are the hallmark of autoimmunity in type 1 diabetes. A more comprehensive understanding of the global iAb prevalence could help reduce avertible morbidity and mortality among children and adolescents with type 1 diabetes. We present the first scoping review that provides a global synthesis of the prevalence of iAb in children and adolescents with type 1 diabetes. Research Design and Methods We searched Ovid MEDLINE® with Daily Update, Embase (Elsevier, embase.com) and PubMed (National Library of Medicine -NCBI), for studies pertaining to prevalence in children and adolescents (0-19) with type 1 diabetes published between 1 Jan 1990 and 18 June 2021. Results were synthesized using Covidence systematic review software and meta-analysis was completed using R v3·6·1. Results The review revealed 125 studies from 48 different countries (92 from high-income countries). Globally, in new-onset type 1 diabetes, IA-2A was the most prevalent iAb 0·714 (95% CI [0·71, 0·72]), followed by ICA 0·681 (95% CI [0·67, 0·69]), ZnT8A was 0·654 (95% CI [0·64, 0·66]) , GADA 0·636 (95% CI [0·63, 0·66]) and then IAA 0·424 (95% CI [0·42, 0·43]), with substantial variation across world regions. The weighted mean prevalence of IA-2A was more variable, highest in Europe at 0·749 (95% CI [0·74, 0·76]) followed by Northern America 0·662 (95% CI [0·64, 0·69]), Latin America and the Caribbean 0·632 (95% CI [0·54, 0·72]), Oceania 0·603 (95% CI [0·54, 0·67]), Asia 0·466 (95% CI [0·44, 0·50]) and Africa 0·311 (95% CI [0·23, 0·40]). In established cases of type 1 diabetes, GADA was the most prevalent iAb 0·407 (95% CI [0·39, 0·42]) followed by ZnT8A 0·322 (95% CI [0·29, 0·36]), IA-2A 0·302 (95% CI [0·29, 0·32]), IAA 0·258 (95% CI [0·24, 0·26]) and ICA 0·145 (95% CI [0·13, 0·16]), again with substantial variation across regions. Conclusion Understanding the global prevalence of iAb in children and adolescents with type 1 diabetes could help with earlier identification of those at-risk of developing type 1 diabetes and inform clinical practice, health policies, resource allocation, and targeted healthcare interventions to better screen, diagnose and manage children and adolescents with type 1 diabetes